A New Tool for Coding and Interpreting Injuries in Fatal Airplane Crashes: The Crash Injury Pattern Assessment Tool Application to the Air France Flight AF447 Disaster (Rio de Janeiro–Paris), 1st of June 20091. Issue 5 (16th July 2014) - Schuliar, Yves; Chapenoire, Stéphane; Miras, Alain; Contrand, Benjamin; Lagarde, Emmanuel
Abstract For investigation of air disasters, crash reconstruction is obtained using data from flight recorders, physical evidence from the site, and injuries patterns of the victims. This article describes a new software, Crash Injury Pattern Assessment Tool (CIPAT), to code and analyze injuries. The coding system was derived from the Abbreviated Injury Score (AIS). Scores were created corresponding to the amount of energy required causing the trauma (ER), and the software was developed to compute summary variables related to the position (assigned seat) of victims. A dataset was built from the postmortem examination of 154/228 victims of the Air France disaster (June 2009), recovered from the Atlantic Ocean after a complex and difficult task at a depth of 12790 ft. The use of CIPAT allowed to precise cause and circumstances of deaths and confirmed major dynamics parameters of the crash event established by the French Civil Aviation Safety Investigation Authority.